Precise hourly personalized embryo transfer significantly improves clinical outcomes in patients with repeated implantation failure - Xu, Yameng; Du, Jing; Zou, Yangyun; Lin, Xiaoli; Chen, Yulin; Ma, Lan; Jiang, Shan; Lin, Xiufeng (Frontiers in Endocrinology, 2024)
Purpose This study investigated whether RNA-Seq-based endometrial receptivity test (rsERT)—which provides precision for the optimal hour of the window of implantation (WOI)—can improve clinical outcomes of frozen embryo transfer (FET) cycles in patients with a history of repeated implantation failure (RIF). Methods Patients with a history of RIF who received at least one autologous high-quality blastocyst during the subsequent FET cycle were retrospectively enrolled and divided into two groups: rsERT and FET, comprising patients who underwent rsERT-guided pET (n=115) and standard FET without rsERT (n=272), respectively. Results In the rsERT group, 39.1% (45/115) of patients were receptive. rsERT patients showed a higher probability of achieving both positive human chorionic gonadotropin (63.5% vs. 51.5%, P=0.03) and clinical pregnancy (54.8% vs. 38.6%, P=0.003) rates. In subgroup analysis, rsERT patients with non-receptive results had higher clinical pregnancy rates than patients undergoing FET (58.6% vs. 38.6%, P=0.003). rsERT patients with receptive results guided by rsERT with a precise WOI time had higher, although non-significant, clinical pregnancy rates (48.9% vs. 38.6%, P=0.192) than patients who underwent standard-time FET. Conclusion Hourly precise rsERT can significantly improve the probability of achieving clinical pregnancy in patients with RIF, especially in those with non-receptive rsERT results.